Craniofrontonasal syndrome in a male due to chromosomal mosaicism involving EFNB1: further insights into a genetic paradox - Evers, Christina; Jungwirth, Maria Sophia; Morgenthaler, J.; Hinderhofer, Katrin; Maas, B.; Janssen, Johannes W. G.; Jauch, Anna; Hehr, Ute; Steinbeisser, Herbert; Moog, Ute (Clinical genetics, 2014)
Craniofrontonasal syndrome (CFNS) is an X-linked disorder caused by inactivating mutations in the gene for ephrin-B1 (EFNB1). Paradoxically it shows a more severe phenotype in females than in males. As a result of X inactivation cell populations with and without EFNB1 expression are found in EFNB1+/− females. This is thought to initiate a process termed cellular interference which may be responsible for the phenotype in females. We present a boy with severe clinical features of CFNS. In ∼42% of his blood cells we found a supernumerary ring X chromosome containing EFNB1 but lacking XIST. Mosaicism for cell populations with different levels of EFNB1 expression can explain the severe phenotype of this patient. In vitro experiments in Xenopus tissue showed that cells overexpress ephrinB1 cluster and sort out from wild-type cells. Our report provides further evidence that cellular interference contributes to the paradoxical inheritance pattern of CFNS.